Isolated bilateral simplex ureteric ectopia: Bladder capacity as an indicator of continence outcome. Issue 5 (October 2017) - Stavrinides, Vasilis; Charlesworth, Paul; Wood, Dan; Desai, Divyesh; Cherian, Abraham; Mushtaq, Imran; Cuckow, Peter; Smeulders, Naima
Summary: Introduction: Isolated bilateral simplex ectopic ureters (BSEUs) are rare but pose a therapeutic challenge: ureteric reimplantation alone does not accomplish continence in all. Identifying the patients needing additional procedures for continence early could prevent multiple operations. Objective: Potential preoperative indicators for postoperative continence are explored in eight BSEU girls without cloacal, anorectal, or spinal anomalies. Study design: With institutional approval, all patients with BSEU between 1985 and 2012 were retrospectively reviewed. Cystoscopy determined the site of ureteric ectopia (6 of 16 at the bladder neck [BN], 5 of 16 below the BN, and 5 of 16 in the distal urethra). Bladders were assessed by a combination of ultrasound, urodynamics, micturating cystourethrogram, cystoscopic, and intraoperative observations. Expected bladder capacity for age (EBCA) was calculated by 30 ml + (30 ml × age in years) or 38 ml + (2.5 ml × age in months) for children greater or less than 2 years, respectively. Continence outcomes were appraised at a minimum of 4 years. The small number of patients precludes credible statistical analysis and therefore raw data are presented. Results: Patients underwent cross-trigonal ureteric reimplantation at 1–5.5 years, in five without BN surgery and in three with a Young–Dees–Leadbetter BN tightening. Of those without BN surgery at reimplantation, four achieved satisfactory continence for their age, but one has had multiple procedures culminating in BN closure, ileocystoplasty, and Mitrofanoff. Among the BN-tightening group, one was in nappies at 4 years, one had residual stress incontinence after two further BN injections, and one proceeded to artificial urinary sphincter after two BN injections. Five patients had significant renal impairment. Discussion: Patients with satisfactory continence after reimplantation alone and those needing further procedures tended to differ in their preoperative observations of bladder capacity and apparent BN competence. This study suggests preoperative observations of an empty bladder on serial ultrasound and/or a wide-open BN with small or even moderate bladder capacity at cystoscopy to indicate the need for BN surgery. In contrast, children with bladder filling to at least 30% of expected bladder capacity for age on preoperative ultrasound or apposition of the BN at cystoscopy may achieve satisfactory continence after ureteric reimplantation alone. Bladder capacity as an indicator of BN competence can also be correlated to continence outcomes in previously published series. Polyuria associated with renal impairment can exacerbate the challenge for continence. Conclusion: Preoperative bladder capacity appears to be an indicator of inherent BN function and a thorough assessment of the urinary tract by cystoscopy, ultrasound, micturating cystourethrogram, and functional imaging may guide the surgeon on the need for BN surgery at the time of ureteric reimplantation. Where continence remains elusive, patients should be counselled that a further BN injection is occasionally of value although more significant BN procedures are required for most. Table Continence outcomes for individual patients at their last FU. Cystoscopic observations regarding bladder size/BN competence and observed bladder volumes prior to cross-trigonal ureteric reimplantation with or without BN tightening. Continence outcome Patient Age at FU Pre-ureteric reimplantation cystoscopic finding bladder filling on US Postoperative bladder function assessment After ureteric reimplantation alone Continent 1 4 y Not recorded 21 ml at 7 mo (36% EBCA) 100 ml at 4 y (67% EBCA) 2 6 y Good capacity 14 ml at 3 mo (30% EBCA) 281 ml at 6 y (130% EBCA) 4 11 y Not recorded 71 ml at 2.5 y (68% EBCA) 450 ml at 11 y (125% EBCA) Enuretic 5 8 y BN apposition 230 ml at 5 y (125% EBCA) Capacity maintained Proceeding to BNC cystoplasty 8 20 y Small capacity BN wide open Not recorded 220 ml at 14 y (50% EBCA) after colposuspension Reimplantation with BN tightening In nappies 3 4 y Moderate size BN wide open 14 ml at 12 mo (20% EBCA) 47 ml at 2.5 y (50% EBCA) Proceeding to BNI 6 20 y Moderate size BN wide open Not recorded Urodynamics: at 8 y 100% EBCA and at 20 y stress leak Proceeding to AUS 7 16 y Small capacity Empty on serial US at 5 y 188 ml at 12 y (50% EBCA) after BNI The EBCA is calculated for children aged below 2 years (38 ml + 2.5 ml × age in months) and those above 2 years (30 ml + 30 ml × age in years). Bladder filling is expressed as a percentage of EBCA (measured volume/EBCA × 100). AUS = artificial urinary sphincter; BN = bladder neck; BNC = bladder neck closure; BNI = bladder neck injection; EBCA = expected bladder capacity for age; FU = follow-up; mo = months; US = ultrasound; y = years.